2021
DOI: 10.1532/hsf.3873
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Atrial Fibrillation after On-Pump Versus Off-Pump Coronary Artery Bypass Grafting

Abstract: Background: This study aimed to investigate the incidence of postoperative atrial fibrillation (POAF) in patients undergoing off-pump versus on-pump coronary artery bypass grafting (CABG) under cardiopulmonary bypass (CPB). Methods: A total of 3,197 consecutive patients (1,816 males, 1,381 females; mean age: 60.8 ± 9.8 years) with preoperative sinus rhythm who underwent CABG at a cardiovascular surgery clinic between November 2009 and March 2014 retrospectively were analyzed. Of the patients, 1,680 underwent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Low-dose dopamine and norepinephrine have been reported to be associated with the risk of POAF after cardiac surgery. 24,25 AA after PTE was associated with longer LOS and more postoperative complication. 7 Moreover, during the follow-up with a median of 4.2 (1.6-6.3) years, Havranek et al 8 found that AF and atrial tachycardia in CTEPH patients treated with PTE were associated with reduced cardiac functional capacity.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Low-dose dopamine and norepinephrine have been reported to be associated with the risk of POAF after cardiac surgery. 24,25 AA after PTE was associated with longer LOS and more postoperative complication. 7 Moreover, during the follow-up with a median of 4.2 (1.6-6.3) years, Havranek et al 8 found that AF and atrial tachycardia in CTEPH patients treated with PTE were associated with reduced cardiac functional capacity.…”
Section: Discussionmentioning
confidence: 91%
“…A majority of CTEPH patients received phenylephrine, rather than low‐dose dopamine and norepinephrine, to maintain systemic blood pressure after PTE surgery. Low‐dose dopamine and norepinephrine have been reported to be associated with the risk of POAF after cardiac surgery 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…This clearly explains why the POAF patient's mean age is approximately 4.5 years older than that of the non-POAF group. Early mortality has a significant correlation with age as well (12). When age and other risk factors for early mortality are taken into account, it becomes clear that POAF is not an independent cause of early death.…”
Section: Discussionmentioning
confidence: 99%
“…[34] Arslan G's study results suggest that on-pump CABG under CPB is correlated with POAF. [35] Postoperative AF was developed in twenty-five patients (11%). The incidence of POAF was 9.5% and 11.5% in SinaCurcumin™ and placebo groups, respectively.…”
Section: Discussionmentioning
confidence: 99%